Somatotype and body composition as an indicator to determine the role of performance in the men's basketball team in the youth team Del Campo School - Menéndez-Amador, C. E.; Figueroa-Soriano, R. O.; Gaitan-Amador, R. A. (Journal of Human Sport & Exercise, 2021)
The following descriptive study, with a quantitative approach that allowed to offer pertinent information to the somatotype and the body composition of the basketball player, in such a way that it allows a survey of both the player's profile in a general way and specifically, according to the role that plays in the team and would contribute to the diagnosis of the team in terms of planning workloads in training. The sample is of a non-probabilistic type directed, the selection procedure by quota intentionally, made up of 12 students who are part of the men's basketball team at Del Campo of Tegucigalpa school. The Carter method for somatoplotting and the Parizkova and Buzkova method were applied, where the results were favourable considering that the tests offer useful information such as the presence of five players with a percentage of body fat (KG GRSA) above from the mean with respect to age, the rest with favourable levels of% ACM for basketball practice.